High-intensity laser experiments with highly charged ions in a Penning trap - Ringleb, Stefan; Kiffer, M.; Stallkamp, N.; Kumar, S.; Hofbrucker, J.; Reich, Bianca; Arndt, B.; Brenner, G.; Ruiz-Lopéz, M.; Düsterer, S.; Vogel, Manuel; Tiedtke, K.; et al. (Physica scripta, 2022)
We have conceived and built the HILITE (High-Intensity Laser-Ion Trap Experiment) Penning-trap setup for the production, confinement and preparation of pure ensembles of highly charged ions in a defined quantum state as a target for various high-intensity lasers. This enables a broad suite of laser-ion interaction studies at high photon energies and/or intensities, such as non-linear photo-ionisation studies. The setup has now been used to perform experiments at one such laser facility, namely the FLASH Free-Electron Laser at DESY in Hamburg, Germany. We describe the experimental possibilities of the apparatus, the results of the first measurements and future experiments at other laser facilities.
Gesehen am 03.08.2022